An analysis of Malaysia’s falling fertility rate: does inflation matter? - Yip, Tien Ming; Lai, Siow Li (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study provides a macro analysis of the determinants of fertility, highlighting the role of inflation in influencing the fertility level. This study uses state-level dataset from Malaysia over the sample period of 2011-2021 and the panel Fixed Effect estimator to quantify the extent to which inflation affects fertility rate. Fertility rate is found to have a negative and significant association with inflation. The negative impact of inflation on fertility is widespread across regions in Malaysia. Further analysis provides additional insight that the negative effect of inflation on fertility is stronger in the long-run period. The results remain robust to alternative measure of fertility rate and estimation method. This study adds to the growing literature on the determinants of fertility at the macro level by emphasizing the crucial role of inflation and highlighting its short- and long-run implications on fertility rates. While it is a huge challenge to reverse the fertility decline in the age of rising cost of living, this study proposes several policy recommendations, such as providing monthly child allowance, expanding the coverage of the childcare subsidy to women working in all economic sectors, and initiating savings programmes that help families to build up a buffer stock of savings to cater for children’s expenses, aiming to depress the pace of fertility decline and maintain the long-run fertility rate at a sustainable level.